« Frei Luís de Sous » a d’Almeida Garrett. Pour une approche pragmatique du texte dramatique - DOBROIU, Vlad (Studia Universitatis Babeș-Bolyai Dramatica, 2020)
Frei Luís de Sousa by Almeida Garrett: a pragmatic analysis of the theatre dialogue. In this article, we analyse, from a pragmatic point of view, the dialogue of the play Frei Luís de Sousa by Almeida Garrett and its translation made by Maxime Formont at the beginning of the 20th century and published in Livourne. We focus on the strategies used by the participants in the theatre discourse in order to consolidate and sometimes even to renegotiate their interpersonal relationship. Our main interest concerns the use of nouns and pronouns in the 1st Act. For a better understanding of the socio-historical context of this play, we propose a short introduction to the 19th century, in Portugal. We also present and analyse some important para-textual pieces of information that accompany the translation made by Maxime Formont.